Effects of Multiple-Device Integration Strategies on Driver Comprehension of Crash Warnings. (September 2013) - Singer, Jeremiah; Lerner, Neil; Robinson, Emanuel
This experiment investigated the extent to which driver comprehension of imminent crash warnings is affected by the degree of integration when there are multiple Connected Vehicle products in the vehicle. Two displays were placed in an experimental vehicle: one representing original equipment and one representing a portable, nomadic device. Participants were randomly assigned to one of five device integration conditions. Participants drove on a test track and were occasionally presented with either a nonurgent message or an urgent crash warning. Participants recognized warnings most quickly when only one display was active in the car; when both displays were active, response times generally improved when messages and warnings were integrated into a single physical location. Warning recognition times were longer when a warning closely followed a non-urgent message on the other display than when a warning followed a non-urgent message on the same display. When messages and warnings from both source displays were integrated into a single display, this effect was not observed, suggesting that the separate display locations are responsible for the increased warning recognition time rather than the different formats of the messages from each source device.